Enhanced Antibacterial and Antibiofilm Activities of CdS Nanoparticles Synthesized Via Solvothermal and Co-precipitation Routes - Omar, Sleman Yousif; Pekdemir, Mustafa Ersin; Ahmed, Asmaa Sayed; Babakr, Karukh Ali; Razaq, Chawan Hazhar; Saleh, Kochar Khasro; Ali, Bala Talib (Springer, 2025)
Antibiotic-resistant infections are a global crisis, creating an urgent need for alternative antimicrobials. In this study, cadmium sulfide (CdS) nanoparticles (NPs) were synthesized via co-precipitation and solvothermal routes and calcined at 100 degrees C, 200 degrees C, and 300 degrees C to evaluate their antimicrobial efficacy. Structural characterization confirmed the hexagonal wurtzite CdS phase with crystallite size ranging from 11.9 to 41.3 nm. We tested the antibacterial and antibiofilm activity against Escherichia coli (E. coli, ATCC 25322) and Bacillus cereus (B. cereus, ATCC 14579). Disk diffusion assays showed no inhibition for co-precipitated samples (BA1-BA3). In contrast, solvothermally synthesized NPs (BA4-BA6) exhibited strong activity, with inhibition zones up to 28 mm against E. coli and 33 mm against B. cereus at 10 mu g/mL. The minimum inhibitory concentration (MIC) ranged 100-800 mu g/mL (BA6: MIC = 100 mu g/mL, MBC = 200 mu g/mL against both strains). In antibiofilm assays, BA4-BA6 markedly suppressed biofilm formation, with BA5 and BA6 most effective. Overall, solvothermal CdS NPs showed similar to 100% higher antibacterial efficacy than co-precipitated NPs. These findings demonstrate that synthesis method and calcination critically influence CdS NP performance, positioning solvothermal CdS NPs as promising safe and efficient antimicrobial agents for biomedical applications.
Keywords: CdS nanoparticles; Calcination; Antibacterial activity; Antibiofilm; Escherichia coli; Bacillus cereus; Biomedical applications